2023
DOI: 10.3390/cancers15245848
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Melanoma Diagnosed between 2010 and 2014 in a Colombian Cancer Registry and a Call for Improving Available Data on Melanoma in Latin America

Esther de Vries,
Claudia Uribe,
Claudia Catalina Beltrán Rodríguez
et al.

Abstract: We aimed to improve the available information on morphology and stage for cutaneous melanoma in the population-based cancer registry of the Bucaramanga Metropolitan Area in Colombia. The incidence and survival rates and the distribution of melanoma patients by age, gender, anatomical subsite, and histological subtype were calculated. All 113 melanoma patients (median age 61) were followed up (median time 7.4 years). This exercise (filling in missing information in the registry by manual search of patient clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They discovered that melanomas at different anatomical locations possess distinct risk factors ( 35 ). Epidemiological studies have shown that most melanomas are located on the lower limbs, followed by the trunk, with melanomas of the head and neck and those with unspecified anatomical locations having the poorest survival rates ( 36 ). Trunk SKCMs tend to have less sun exposure compared to facial SKCMs, and studies have confirmed that anti-PD-1 immunotherapy is particularly recommended for melanomas originating from areas of chronic sun exposure ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that melanomas at different anatomical locations possess distinct risk factors ( 35 ). Epidemiological studies have shown that most melanomas are located on the lower limbs, followed by the trunk, with melanomas of the head and neck and those with unspecified anatomical locations having the poorest survival rates ( 36 ). Trunk SKCMs tend to have less sun exposure compared to facial SKCMs, and studies have confirmed that anti-PD-1 immunotherapy is particularly recommended for melanomas originating from areas of chronic sun exposure ( 37 ).…”
Section: Discussionmentioning
confidence: 99%